Ectopia cordis (University Heart Journal, 2015)
Ectopia cordisis characterized by partial or complete displacement of the heart out of the thoracic cavity The defect is a rare congenital abnormality, occurring in 5.5 to 7.9 per 1 million live births.University Heart Journal Vol. 9, No. 2, July 2013; 119-120